Bioactive coatings with anti-osteoclast therapeutic agents for bone implants: Enhanced compliance and prolonged implant life. (February 2022) - Bjelić, Dragana; Finšgar, Matjaž
Abstract: The use of therapeutic agents that inhibit bone resorption is crucial to prolong implant life, delay revision surgery, and reduce the burden on the healthcare system. These therapeutic agents include bisphosphonates, various nucleic acids, statins, proteins, and protein complexes. Their use in systemic treatment has several drawbacks, such as side effects and insufficient efficacy in terms of concentration, which can be eliminated by local treatment. This review focuses on the incorporation of osteoclast inhibitors (antiresorptive agents) into bioactive coatings for bone implants. The ability of bioactive coatings as systems for local delivery of antiresorptive agents to achieve optimal loading of the bioactive coating and its release is described in detail. Various parameters such as the suitable concentrations, release times, and the effects of the antiresorptive agents on nearby cells or bone tissue are discussed. However, further research is needed to support the optimization of the implant, as this will enable subsequent personalized design of the coating in terms of the design and selection of the coating material, the choice of an antiresorptive agent and its amount in the coating. In addition, therapeutic agents that have not yet been incorporated into bioactive coatings but appear promising are also mentioned. From this work, it can be concluded that therapeutic agents contribute to the biocompatibility of the bioactive coating by enhancing its beneficial properties. Graphical Abstract: ga1 Highlights: Osteoclast activity is a major cause of implant failure and poor osseointegration. Osteoclast inhibition depends on drug concentration and controlled release. The release of therapeutic agents depends on the coating material.